THE INFLUENCE OF RATIONAL MOTIVES AND EMOTIONAL MOTIVES ON PURCHASE DECISION OF VIRTUAL GOODS IN MOBILE LEGENDS ONLINE GAMES - Mokodompit, Ichsan R.; Massie, James D. D.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
This research uses rational and emotional factors to analyse player's decision making in buying virtual goods. This research identifies rational and emotional motives that are considered by players that it can influence them to decide to buy virtual goods in Mobile Legends. This research is using a quantitative approach. The sample of this research is 100 respondents. The descriptions of 100 respondents are classified based on age and occupation. The findings of this research shows that (1) Rational motives partially have a significant effect on purchase decision (2) Emotional motives partially have a significant effect on purchase decision (3) Rational motives and emotional motives simultaneously has a significant effect on purchase decision.Â Keywords: rational buying motives, emotional buying motives, purchase decision, online games, virtual goods